P-062 Race Does Not Affect the Prevalence of Sporadic Adenomas in Inflammatory Bowel Disease. (March 2016) - Waseem, Najeff; Nassereddine, Samah; Pavle, Alexis; Zhang, Jennie; Dougherty, Timothy; Borum, Marie
Abstract : Background: Sporadic adenomas are associated with an increased risk for the development of colorectal cancer. Some data suggests African Americans are at increased risk for large adenomas, more proximal lesions, and increased prevalence. There is however, to our knowledge, no study that has evaluated the difference in adenoma formation by race in inflammatory bowel disease (IBD) patients. The study analyzes the prevalence of adenomas in IBD patients of Caucasian and African American at an urban university medical center. Methods: A retrospective review was completed using an electronic health record. Consecutive inflammatory bowel disease patients undergoing surveillance colonoscopy during a one-year period at an urban university medical center were evaluated. Patients were excluded if the colonoscopy record could not be matched to an outpatient chart. Data regarding patient ethnicity and other demographics, IBD type and location, and colonoscopic and pathologic findings were compiled in a database created with Microsoft Excel. Patient confidentiality was maintained. Statistical analysis was performed using Fisher's Exact Test, with statistical significance set at P < 0.05. The study was approved by the university IRB. Results: There were 136 with IBD were included, 34 (25%) were African American, 68 (50%) Caucasian, and 34 (25%) classified as other or unknown ethnicity. Of the 136 patients, 58 (42.6%) had Crohn's disease and 78 (57.4%) patients had ulcerative colitis. A total of 12 (8.8%) patients had sporadic adenomas; there were 8 patients (5.9%) with sessile serrated adenomas and 4 (2.9%) with tubular adenoma. Four African Americans (11.8%) and 8 Caucasians (11.8%) had sporadic adenomas. African American patients average age was 46.7 years (95% confidence interval 5.0) and had disease for 14.3 (±3.1) years. White patients age averaged 48.5 years (±3.6) and duration of disease was 17.8 (±2.6). There was no significant difference in the age, disease duration, and type of IBD ( P = 0.6789) between African American and Caucasian patients. Conclusions: IBD is known to increase the risk of developing colorectal cancers, especially through the inflammation-dysplasia pathway. Well-studied risk factors for CRC in IBD include duration, severity and extent of colitis. A relationship between race and CRC risk has been demonstrated in the general population, but not in IBD patients. In addition, there is little data on differences in sporadic adenoma formation between IBD patients of different races. While some literature suggests a difference in the prevalence of sporadic adenomas among African Americans and Caucasians in the general population, this study revealed no such difference in sporadic adenomas based upon race in IBD patients. At present, race does not seem to be an independent risk factor. Gastroenterologists must continue to remain vigilant for the identification of sporadic neoplasia in all patients, including those with IBD.